The spillover effects of U.S. monetary policy on emerging market economies. (28th February 2019) - Tillmann, Peter; Kim, Geun‐Young; Park, Hail
Abstract: The recent implementation of unconventional monetary policies in advanced economies and the preparations for an eventual return to normalization have renewed the interest in spillover effects of monetary policy on emerging market economies. This paper estimates a series of VAR‐X models for a set of 10 emerging economies, that is, VARs in which U.S. policy enters exogenously. The contribution of this paper is (a) to use an identified shock component of the U.S. (shadow) federal funds rate as a consistent policy instrument for conventional and unconventional policies, (b) to account for changes in the transmission of U.S. monetary policy over time, and (c) to quantify asymmetries in the transmission of tightening and easing shocks. The results point to substantially nonlinear and asymmetric spillover effects, which pose challenges to policymakers.